2019
DOI: 10.31764/mj.v2i2.805
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Tingkat Pengetahuan Ibu Hamil Tentang Tanda-Tanda Bahaya Kehamilan Trimester I Di Puskesmas Karang Pule

Abstract: Semakin tinggi pengetahuan ibu tentang tanda bahaya dalam kehamilan, maka semakin rendahnya kejadian bahaya pada ibu hamil. Tujuan untuk mengetahui gambaran tingkat pengetahuan ibu hamil tentang tanda-tanda bahaya kehamilan trimester I di Puskesmas Karang Pule. Penelitian ini menggunakan metode deskriptif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua ibu hamil trimester I yang datang berkunjung ke Puskesmas Karang Pule tahun 2016. Teknik pengambilan sampel yang digunakan adalah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The respondent's age category, which is dominated by healthy reproductive age, is still able to actively learn and receive new knowledge through online media. This healthy reproductive period is 20-35 years, which makes the risk of pregnancy and childbirth both for the mother and for the child lower than for mothers who are pregnant at the age of fewer than 20 years and more than 35 years (Andaruni, Pamungkas, & Lestari, 2017) . Adequate age will have an impact on the level of maturity of a mother's way of thinking and working.…”
Section: Resultsmentioning
confidence: 99%
“…The respondent's age category, which is dominated by healthy reproductive age, is still able to actively learn and receive new knowledge through online media. This healthy reproductive period is 20-35 years, which makes the risk of pregnancy and childbirth both for the mother and for the child lower than for mothers who are pregnant at the age of fewer than 20 years and more than 35 years (Andaruni, Pamungkas, & Lestari, 2017) . Adequate age will have an impact on the level of maturity of a mother's way of thinking and working.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that pregnant women have a good level of knowledge who are young and mature because they will be easy to receive information, especially about their pregnancy (Christina & Sukartiningsih, 2014) The results of the univariate analysis showed that more than half of the respondents had high school education (60%). Qomariah Rista Andaruni et al, (2017) stated that the higher a person's education level, the easier it is to receive information so that the more knowledge they have, on the other hand, less education will hinder a person's development of newly introduced values. This is in line with research (Nuraeni et al, 2017) which suggests that pregnant women who have a high level of education tend to have their pregnancy checked more than those with low education.…”
Section: Discussionmentioning
confidence: 99%
“…Upaya dalam menurunkan kejadian resiko kehamilan adalah pengenalan adanya resiko tinggi pada ibu hamil yang dilakukan melalui skrining/deteksi dini adanya faktor resiko secara pro/aktif pada semua ibu hamil sedini mungkin (Fajrin, 2018) (Andaruni, Pamungkas and Lestari, 2017).…”
Section: Pendahuluanunclassified